2002
DOI: 10.1016/s0006-291x(02)00661-7
|View full text |Cite
|
Sign up to set email alerts
|

Clonal heterogeneity in differentiation potential of immortalized human mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) are bone marrow stroma-derived cells, which can differentiate into several types of mesenchymal tissues. Although regarded as tissue-specific stem cells, human MSCs (hMSCs) have a low proliferative ability with a finite life span, which is a hurdle to further analysis of their biology. Here we attempted to establish immortalized hMSCs by retrovirus-mediated gene transfer. The gain in telomerase activity obtained on expression of human telomerase reverse transcriptase (hTERT) was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
218
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 252 publications
(232 citation statements)
references
References 33 publications
10
218
2
2
Order By: Relevance
“…The loss of differentiation activity in this case is likely to be because of the influence of the viral oncoprotein E6E7, (35,36) although E6E7 has been shown to immortalize some cell types without loss of differentiation potential. (18,37) We have previously shown that cementoblast progenitors are present in BDFCs and that they are phenotypically different from osteoblasts. (10) In this study, we successfully isolated a cementoblast cell line, BCPb8, which seems to behave similarly to the cementum progenitors present in BDFCs, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of differentiation activity in this case is likely to be because of the influence of the viral oncoprotein E6E7, (35,36) although E6E7 has been shown to immortalize some cell types without loss of differentiation potential. (18,37) We have previously shown that cementoblast progenitors are present in BDFCs and that they are phenotypically different from osteoblasts. (10) In this study, we successfully isolated a cementoblast cell line, BCPb8, which seems to behave similarly to the cementum progenitors present in BDFCs, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of telomerase alone is sufficient for immortalization of human foreskin fibroblasts. HPV16 E6 and E7 have been used to inhibit p53 and RB, respectively, to prolong the life span of marrowderived MSCs (Okamoto et al, 2002;Takeda et al, 2004), endometrial gland cells (Kyo et al, 2003), mammary epithelial cells, and keratinocytes (Kiyono et al, 1998). Bmi-1 also has been used to inhibit p16 INK4a transcription to prolong the life span of marrow-derived MSCs.…”
Section: Is Successful Prolongation Of Ucbmscs Life Span Without Inhimentioning
confidence: 99%
“…E6 also accelerates degradation of p53, which induces the cdk inhibitor p21 (Sekiguchi and Hunter, 1998). This system in which p16 INK4a /RB is inhibited and telomerase is activated is highly efficient in extending the life span of hMSCs (Okamoto et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hiMSC 10 was maintained in Dulbecco's modified Eagle's medium (Sigma-Aldrich Inc., St Louis, MO, USA) supplemented with 10% fetal bovine serum (JRH Biosciences, Lenexa, KS, USA) .…”
Section: Cell Culturementioning
confidence: 99%